Synthesis and biological properties of novel brefeldin a analogues - Seehafer, Kai; Rominger, Frank; Helmchen, Günter; Langhans, Markus; Robinson, David G.; Özata, Başak; Brügger, Britta; Klein, Christian D. (Journal of medicinal chemistry, 2013)
New brefeldin A (1) analogues were obtained by introducing a variety of substituents at C15. Most of the analogues exhibited significant biological activity. (15R)-Trifluoromethyl-nor-brefeldin A (3), (15R)-vinyl-nor-brefeldin A (5), their epimers 4 and 6 as well as (15S)-ethyl-nor-brefeldin A (2) were prepared from the key building blocks 12 or 24 by Julia-Kocienski olefination with tetrazolyl sulfones and subsequent macrolactonization. The vinyl derivative 5 allowed analogues to be synthesized by hydroboration and Suzuki-Miyaura coupling. The following biological properties were assessed: (a) inhibition of cell growth of human cancer cells (NCI), (b) induction of morphological changes of the Golgi apparatus of plant and mammalian cells, and (c) influence on the replication of the enterovirus CVB3. Furthermore, conformational aspects were studied by X-ray crystal structure analysis and molecular mechanics calculations, including docking of the analogues into the brefeldin A binding site of an Arf1/Sec7-complex.